COVID‐19 policy responses, mobility, and food prices. Issue 2 (1st December 2021) - Dietrich, Stephan; Giuffrida, Valerio; Martorano, Bruno; Schmerzeck, Georg
Abstract: Governments around the world have taken drastic measures to contain the spread of COVID‐19. Policy responses to the pandemic could affect local food prices in important ways. In this paper, we hypothesize that food prices in regionally integrated markets are more sensitive to mobility constraints than those in segmented markets. We use World Food Programme price data from 774 retail markets in 44 low and middle‐income countries to test whether and how food prices have been affected by the stringency of COVID‐19 containment measures. We assess market segmentation based on pre‐COVID‐19 price data and measure government responses using the Oxford Coronavirus Government Response Tracker. Our results show that more stringent policy responses increase food prices for integrated markets but not for segmented markets. The impact of the stringency of policy responses on food prices seems to be mediated by reductions in mobility and moderated by the dependence of markets on trade before COVID‐19.